PENGARUH PELATIHAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - MUHAMMAD ROCHIMIN; SUKRISPIYANTO - (STIE Indonesia Malang, 2022)
The purpose of this research is. 1) To find out and analyze the significance of the influence of the variable job training and work motivation partially on employee performance, 2) To find out and analyze the significance of the influence of the variable job training and work motivation simultaneously on employee performance, and 3) To find out and analyze the variables that influence dominant to employee performance. In this study, the sample was employees of CV. Young Garuda Malang, totaling 36 people. Methods of data analysis using multiple regression analysis. From the research results, it can be seen that the variables of job training and work motivation partially have a significant effect on employee performance. 2) From the results of the study, it can be seen that the variables of job training and work motivation simultaneously have a significant effect on employee performance, and 3) From the results of the study, it can be seen that job training variables have a more dominant influence on employee performance. Keywords: job training, work motivation and performance